Microstructure evolution and high-temperature tensile properties of Ti-22Al-25Nb alloy joint by electron beam welding - Shiqing WANG; Yi ZHANG; Guodong WEN; Qiang ZHANG; Junlei QI; Wang GAO; Wei QIANG (Hanjie xuebao)
In this paper, the microstructure evolution of the Ti-22Al-25Nb alloy joint by electron beam welding was studied by numerical simulation and experiment. The vacuum electron beam welding of a 5 mm-thick Ti-22Al-25Nb alloy plate was carried out. The effect of the electron beam current on the surface forming and macroscopic morphology of the joint was studied with other welding parameters kept unchanged. The microstructure and phase of the joint were observed by optical microscope, scanning electron microscope, and X-ray diffractometer. At the same time, comparison of experimental and simulated weld morphology verified the accuracy of this simulation, and the microstructure and phase transition process of the joint were analyzed by combining the thermal cycle curve and the phase diagram. The results show that when the electron beam current is 10 mA, a joint with a small grain size and good forming is obtained. Under the action of the welding thermal cycle, the cooling rate of the weld zone and near heat affected zone is very fast, which is mainly composed of B2 phase. The phase transition from O(α2) to B2 occurs in the far heat affected zone. The high-temperature tensile strength of the joint is about 639 MPa, and the elongation after fracture is about 2.5%, both of which are lower than the tensile properties of the base material. The fracture morphology of the joint is composed of cleavage steps and river-like patterns.